Region of Nuclear Ribosomal DNA (ITS2) and Chloroplast DNA (rbcL and trnL-F) as A Suitable DNA Barcode for Identification of Zingiber loerzingii Valeton From North Sumatera, Indonesia - Prasetya, Eko; Lazuardi, Lazuardi; Harahap, Fauziyah; Rachmawati, Yuanita; Yusuf, Yusnaeni; Al Idrus, Said Iskandar; Prastowo, Puji (Universitas Gadjah Mada, 2023)
Zingiber loerzingii Valeton is one of the species in the Zingiberaceae family found throughout Aceh and North Sumatra, Indonesia, with slimy flowers, yellowish white color, and dark orange stamens. Z. loerzingii is endemic in North Sumatra with a very limited distribution. The International Union for Conservation of Nature and Natural Resources classifies this plant into the vulnerable ones category. This study aims to examine the potential of DNA barcoding from nuclear DNA (ITS2) and DNA chloroplasts (rbcL and trnL-F) to identify Z. loerzingii plants. The research sample was obtained from two main distribution areas of Z. loerzingii in North Sumatra, Indonesia, namely Sibolangit Nature Reserve and Tangkahan Conservation Forest. The results showed that all the DNA barcode markers used were able to classify Z. loerzingii into the same group in the phylogenetic analysis. ITS marker is the most effective marker for classifying Zingiberaceae species compared to rbcL and trnL-F markers. The ITS2 marker has the lowest level of intraspecific and intraspecific genetic distance overlap compared to the rbcL and trnL-F markers. This research is expected to provide information related to the DNA barcode of Z. loerzingii in an effort to conserve this rare plant.